República Argentina, Océano Atlántico Sur, Costa Danco, Archipiélago de Palmer / compilación de reconocimientos ejecutados en viajes de exploración de autoridades hidrográficas - Argentina. Ministerio de Marina (Argentina. Ministerio de Marina, 1949)
3a edición 1949. Relief shown by spot heights and hachures. Depths shown by soundings. Includes conversion table and 1 inset map: Pto. Lockroy. Selected lights shown in purple. "I.F. Valdez Cartógrafo" -- lower right margin. "106." Color; 1:300,000